Mídia e representação social juvenil: recepção do Programa Malhação - Prediger, Solange (2011)
This study focuses on understanding popular class youngsters and their relationship with the communication media television. We have investigated the social representation of youth and, therefore, have a rich example in Malhação whose narrative is guided specifically to that audience. The purpose of this work is to understand what are the representations of youth and social class built by "Malhação" and in which way they collaborate in the construction of social representations of the young. The specific objectives of the work are to verify how the representation of youth and class is constructed in "Malhação"; to demonstrate how the TV show represents the relationship between young people with family and affective relationships, consumption and school empirical categories; to verify how the reception of the TV show is done, from the television, by low income youth, emphasizing the role of social class; to see how the young people find themselves represented in the TV show and how they construct juveniles representations from that, with regard to their relationship with each of the empirical categories mentioned above. The research will be developed through a study of reception based on the ethnography methodology. The techniques used are the in-depth interview, participant observation, field diary, informal conversations, the visual record and the watching of the TV show with the interviewees. As a theoretical basis, we use the cultural studies approach and the Communicative Cultural Mediations model of Jesus Martin-Barbero. The study is developed with six popular class youngsters in the city of Santa Maria. We realized that the 18th season focuses on relations between different social classes. Nevertheless, the season does not use the term class to refer to the social position of the characters. So, it is still masking the real class conflicts, easing the discussion about these differences and showing that they do not matter, since all young people represented in the TV show have equal access to consumer goods and leisure activities. So "Malhação" does not critique the inequality and the youth accept this vision presented in the TV show, because they see themselves represented in it. Thus, despite the reality of middle and upper class largely represented, those interviewed see themselves represented in the TV show mainly regarding consumption and the relationship with family and friends. The disagreement occurs with regard to school (they do not see themselves represented in the relationship of union between teachers and students presented in "Malhação"), the love affairs (some youngsters do not assimilate the relation of love between the protagonists with situations of their reality) and leisure (some young people do not see themselves represented in "Malhação" with regard to leisure habits). But this disagreement is not related, in general, with the issue of social class, and when seeing themselves represented in the TV show, this identification with characters, families and idols of the TV is preferably made by subjective questions, which do not relate to popular culture.